Ultralight and hydrophobic PVDF/PMMA open-cell foams with outstanding heat-insulation and oil-adsorption performances fabricated by CO2 molten foaming. (September 2022) - Shi, Zhanlin; Zhao, Guoqun; Zhang, Lei; Wang, Guilong; Chai, Jialong
Abstract: Heat-insulation and oil-water separation are critical issues in the area of energy conservation and environmental protection. Developing high-expansion open-cell polymer foams with excellent heat insulation and oil-absorption properties is an essential way to solve the above problems. An innovative method for fabricating lightweight PVDF open-cell foam via blending with PMMA followed by a supercritical carbon dioxide molten foaming process was proposed, and ultralight and hydrophobic polymer open-cell foams with outstanding heat insulation and oil-absorption properties were successfully prepared. PMMA not only delays cooling crystallization behavior of PVDF but also improves the melt viscoelasticity. As a result, the open-cell polymer foam with an expansion ratio of up to 43.2, open porosity of 98.6 %, and a density of 0.0361 g/cm 3 can be obtained. Benefiting from high expansion ratio and high open porosity, the blend foam displays a thermal conductivity of 31.07 mW∙m −1 ∙K −1, an adsorption capacity for various oils as high as 8.1–23.1 g/g, and favorable cycle durability. This work provides a green and sustainable method for mass production of better-behaved foam materials for heat insulation and oil-water separation. Graphical Abstract: ga1 Highlights: An innovative method for fabricating lightweight PVDF open-cell foam was proposed. The foam with an expansion ratio of 43.2 and open-porosity of 98.6% was obtained. The ultralight open-cell foams offer outstanding thermal insulation property. The blend foams have high adsorption capacity and favorable cycle durability.